EMPTY SELLA SYNDROME: THE GREAT IMITATOR OF VISUAL COMPLAINTS - Irma, Josiah; Onasis, Serena; Rizki, Dr.Saraswati; Ketaren, Dr.Retno; Budimulia, Patricia (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2023)
Introduction: Empty Sella Syndrome is a rare condition of sella turcica malformation, resulting in pituitary gland shrinkage. It may manifest as neurological symptoms, endocrine disorders, visual disturbances, or even incidental findings during imaging. However, patients rarely come with typical complaints thus an extended course and review of this case is needed to prompt suspicion and aid in the diagnosis of ESS. Case Presentation: A 45-year-old woman with cephalgia, bitemporal hemianopia, previous transient bilateral visual loss, and foggy vision. A history of ovarian cancer was noted. Physical examination showed myopic astigmatism ocular dextra sinistra (ODS) with increased intraocular pressure and bitemporal hemianopia ODS. Posterior chamber examinations were within normal limits. Optical coherence tomography showed nasal retinal nerve fiber layer ODS being the thinnest among the rest, although still within normal limits. Neurological examinations also suggested the presence of central vertigo. This subsequently resulted in a suspicion of space-occupying lesion chiasmal compression through metastasis. Discussion: MRI revealed an empty sella turcica. A laboratory examination was then ordered and showed normal endocrinology results. The diagnosis of Primary Empty Sella Syndrome with ocular hypertension was established. The patient was prescribed timolol, codeine, and dexamethasone. A month later during her follow-up, the patient did not show improvement and was suggested to do an MRI with contrast, however, this patient was lost to follow-up. Conclusion: This case report highlighted the manifestation to raise suspicion and aid in the diagnosis of ESS for an optimal and improved diagnosis and treatment of ESS.